2020
DOI: 10.3390/ani10091572
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Agro-Industrial By-Products to Light Lambs: Influence on Meat Characteristics, Lipid Oxidation, and Fatty Acid Profile

Abstract: The aim of this study was to assess the effects of replacing 44% of conventional feeds in a high-cereal concentrate (CON) with by-products (BYP concentrate; 18% corn distillers dried grains with solubles, 18% dried citrus pulp, and 8% exhausted olive cake) on the meat characteristics and fatty acid (FA) profile of fattening light lambs. Two groups of 12 Lacaune lambs were fed concentrate and barley straw ad libitum from 13.8 to 26.0 kg of body weight. There were no differences (p ≥ 0.130) between groups in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 74 publications
0
7
1
Order By: Relevance
“…In general, in this study, the n-6/n-3 ratio was high for all treatments, which may have occurred due to the low content of omega-3 fatty acids found in our results. In the current work, DHA (C22:6 n-3) was not detectable, and eicosapentaenoic acid (EPA; C20:5 n-3) was found at a low concentration in lamb meat [ 47 - 53 , 57 ] in all treatments, which could explain the undesirably high n-6/n-3 ratio found in this work.…”
Section: Discussioncontrasting
confidence: 51%
“…In general, in this study, the n-6/n-3 ratio was high for all treatments, which may have occurred due to the low content of omega-3 fatty acids found in our results. In the current work, DHA (C22:6 n-3) was not detectable, and eicosapentaenoic acid (EPA; C20:5 n-3) was found at a low concentration in lamb meat [ 47 - 53 , 57 ] in all treatments, which could explain the undesirably high n-6/n-3 ratio found in this work.…”
Section: Discussioncontrasting
confidence: 51%
“…The replacement of the diet at the level of 44% by a mixture of agro-industrial by-products that contained exhausted olive cake did not change growth performance, pH, chemical composition, color, or texture parameters of lamb meat but increased its shelf-life (reduced lipid oxidation levels) and improved its fatty acid profile (decrease of SFAs and increase of PUFAs content) [ 81 , 82 ]. Furthermore, stoned olive cake dietary supplementation (35%) improved the oxidative stability of lamb meat and its combination with linseed (17% and 10%, respectively) improved the fatty acid composition of meat without compromising oxidative stability [ 83 ], with no effect on feed intake, growth performance, or carcass weight [ 84 ].…”
Section: Effects Of Olive By-products Dietary Supplementation In Rmentioning
confidence: 99%
“…One strategy to reduce meat oxidation relies on the addition of antioxidants from natural supplements to the animal diets. Several researchers reported that feeding with natural antioxidants improve meat oxidation in chickens [ 14 ], pigs [ 15 ], lamb [ 16 ], goats [ 17 ] and cattle [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Feeding agro-industrial residues to livestock not only reduces environmental problems caused by residue accumulation and decreases the carbon footprints of animal production [ 19 ] but also improves the shelf-life stability and quality of meat [ 16 , 20 ] due to the presence of bioactive compounds such as phytochemicals and vitamins. Black rice ( Oryza sativa L.) and purple corn ( Zea mays L.) have been described as novel sources of natural antioxidants.…”
Section: Introductionmentioning
confidence: 99%